Method for in-situ construction of ternary heterostructure with light response on titanium surface

By constructing a ternary TiO2/CaWO3/WO3 heterostructure on the titanium surface, the problem of limited effect of a single heterostructure on photogenerating holes and electron separation is solved, and stronger photoresponsiveness and wider wave absorption band are achieved.

CN119571320AActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411751559.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing single heterostructure type has limited effect on the separation of photogenerated holes and electrons, resulting in insufficient photoresponsiveness.

Method used

The ternary TiO2/CaWO3/WO3 heterostructure is constructed in situ by the titanium surface, and a composite structure with light response capability is formed by using microarc oxidation, microwave hydrothermal, ion exchange and heat treatment steps.

Benefits of technology

The wavelength range of the wave absorption band is widened, the light response intensity is improved, and the separation efficiency of photogenerated holes and electrons is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571320A_ABST
    Figure CN119571320A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ construction of a ternary heterostructure with light response on a titanium surface, and relates to a method for constructing a ternary heterostructure. The invention aims to solve the problem that the existing single heterostructure type has a limited effect on separation of photo-generated holes and electrons. The method comprises the following steps: 1, micro-arc oxidation treatment; 2, microwave hydrothermal treatment; 3, ion exchange treatment; and 4, heat treatment. The method is used for in-situ construction of the ternary heterostructure with the light response on the titanium surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for constructing a ternary heterostructure. Background Art

[0002] The commonly used TiO2-based heterojunction with photoresponse has a too large energy band gap and can only absorb light in the ultraviolet band, and the photogenerated holes and electrons are prone to recombination. The common heterostructure types currently include type I, type II and type Z heterostructures. A single heterostructure type has limited effect on separating photogenerated holes and electrons. Therefore, it is urgent to prepare a ternary heterostructure composed of type I and type II or type Z heterostructures, so as to achieve a more negative oxidation potential for photogenerated holes and a more positive reduction potential for photogenerated electrons, and improve the photoresponse ability of the heterostructure. Summary of the invention

[0003] The present invention aims to solve the problem that the existing single heterostructure type has limited effect on separating photogenerated holes and electrons, and further provides a method for in-situ construction of a light-responsive ternary heterostructure on a titanium surface.

[0004] A method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface is carried out in the following steps:

[0005] 1. Micro-arc oxidation treatment:

[0006] The pretreated titanium plate is placed in an electrolyte, the pretreated titanium plate is used as an anode, the stainless steel plate is used as a cathode, and a pulse constant current mode is adopted to perform micro-arc oxidation under the conditions of a current of 0.5A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C, to obtain a titanium plate treated with micro-arc oxidation;

[0007] The electrolyte is composed of ethylenediaminetetraacetate, acetate, tungsten salt, metaphosphate, alkali solution and deionized water;

[0008] 2. Microwave hydrothermal treatment:

[0009] The titanium plate treated by micro-arc oxidation is immersed in a tungstate solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment;

[0010] 3. Ion exchange treatment:

[0011] The titanium plate after microwave hydrothermal treatment is immersed in an acid solution, and finally washed and dried to obtain the titanium plate after ion exchange treatment;

[0012] 4. Heat treatment:

[0013] The titanium plate after ion exchange is placed in a muffle furnace and heat treated for 1h to 8h in an air atmosphere at a temperature of 300°C to 800°C, thereby completing the method of in-situ construction of a light-responsive ternary heterostructure on the titanium surface.

[0014] The beneficial effects of the present invention are:

[0015] The present invention aims to construct a photoresponsive ternary TiO2 / CaWO3 / WO3 heterostructure in situ on the titanium plate surface. A porous coating containing Ca element is prepared on the titanium plate surface by micro-arc oxidation technology, and then a microwave hydrothermal treatment is performed to form a large number of blade-shaped calcium tungstate crystals (Ca tungstate) on the titanium micro-arc oxidation coating surface. 2+ +WO4 2- ―CaWO4), through acid ion exchange technology, control the ion exchange time (CaWO4+2H + ―H2WO4+Ca 2+ ), converted into a calcium tungstate / tungstate composite structure, and after heat treatment, transformed into a TiO2 / CaWO3 / WO3 heterostructure, thereby broadening the absorption band range, improving the light response intensity, and solving the problem that the existing single heterostructure type has limited effect on separating photogenerated holes and electrons.

[0016] The sample treated by the present invention was subjected to EDS spectrum detection, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detection showed the presence of calcium tungstate and tungsten oxide in the sample treated by the present invention. Scanning electron microscopy showed that a large amount of blade-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the surface of the sample treated by the present invention was characterized, and a sample with a size of 10mm×10mm was placed in a subunit blue solution. Under the irradiation of a xenon lamp, the light response intensity of the ternary heterostructure was evaluated based on the degradation ability of the organic dye. Compared with the sample with only titanium dioxide on the titanium plate after micro-arc oxidation treatment, the degradation rate of the organic dye can reach more than 80%. It shows that the sample obtained by the present invention has a certain light response intensity.

[0017] Attached Notes

[0018] Figure 1 This is the EDS spectrum of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in Example 1;

[0019] Figure 2 This is the XRD spectrum of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in Example 1, where A is the anatase peak, B is the titanium peak, C is calcium tungstate, and D is tungsten oxide;

[0020] Figure 3 This is a scanning electron microscope image of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in Example 1;

[0021] Figure 4 The organic dye degradation rate of the titanium plate after micro-arc oxidation treatment prepared in step 1 of Example 1 and the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in step 4. DETAILED DESCRIPTION

[0022] Specific implementation method 1: This implementation method is a method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface, which is carried out in the following steps:

[0023] 1. Micro-arc oxidation treatment:

[0024] The pretreated titanium plate is placed in an electrolyte, the pretreated titanium plate is used as an anode, the stainless steel plate is used as a cathode, and a pulse constant current mode is adopted to perform micro-arc oxidation under the conditions of a current of 0.5A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C, to obtain a titanium plate treated with micro-arc oxidation;

[0025] The electrolyte is composed of ethylenediaminetetraacetate, acetate, tungsten salt, metaphosphate, alkali solution and deionized water;

[0026] 2. Microwave hydrothermal treatment:

[0027] The titanium plate treated by micro-arc oxidation is immersed in a tungstate solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment;

[0028] 3. Ion exchange treatment:

[0029] The titanium plate after microwave hydrothermal treatment is immersed in an acid solution, and finally washed and dried to obtain the titanium plate after ion exchange treatment;

[0030] 4. Heat treatment:

[0031] The titanium plate after ion exchange is placed in a muffle furnace and heat treated for 1h to 8h in an air atmosphere at a temperature of 300°C to 800°C, thereby completing the method of in-situ construction of a light-responsive ternary heterostructure on the titanium surface.

[0032] The beneficial effects of this embodiment are:

[0033] The present embodiment aims to construct a photoresponsive ternary TiO2 / CaWO3 / WO3 heterostructure in situ on the titanium plate surface. A porous coating containing Ca element is prepared on the titanium plate surface by micro-arc oxidation technology, and then microwave hydrothermal treatment is performed to form a large number of blade-shaped calcium tungstate crystals (Ca tungstate) on the titanium micro-arc oxidation coating surface. 2+ +WO4 2- ―CaWO4), through acid ion exchange technology, control the ion exchange time (CaWO4+2H +―H2WO4+Ca 2+ ), converted into a calcium tungstate / tungstate composite structure, and after heat treatment, transformed into a TiO2 / CaWO3 / WO3 heterostructure, thereby broadening the absorption band range, improving the light response intensity, and solving the problem that the existing single heterostructure type has limited effect on separating photogenerated holes and electrons.

[0034] The samples treated by this embodiment were subjected to EDS spectrum detection, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detection showed the presence of calcium tungstate and tungsten oxide in the samples treated by this embodiment. Scanning electron microscopy showed that a large amount of blade-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the surface of the sample treated by this embodiment was characterized, and a sample with a size of 10mm×10mm was placed in a subunit blue solution. Under the irradiation of a xenon lamp, the light response intensity of the ternary heterostructure was evaluated based on the degradation ability of the organic dye. Compared with the sample with only titanium dioxide on the titanium plate after micro-arc oxidation treatment, the degradation rate of the organic dye can reach more than 80%. It shows that the sample obtained by this embodiment has a certain light response intensity.

[0035] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the pretreated titanium plate described in step 1 is specifically prepared according to the following steps: polishing the surface of the titanium plate with 400# and 1000# metallographic sandpaper in sequence, then washing with deionized water, and finally drying at a temperature of 20°C to 30°C for 0.5h to 1h to obtain the pretreated titanium plate. The rest is the same as specific embodiment 1.

[0036] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the titanium plate is made of titanium, titanium alloy, titanium-based medium entropy alloy or titanium-based high entropy alloy. The rest is the same as specific implementation method 1 or 2.

[0037] Specific embodiment 4: This embodiment is different from any one of specific embodiments 1 to 3 in that: the titanium plate is a medium entropy alloy or high entropy alloy of HCP-Ti type, a medium entropy alloy or high entropy alloy of BCC-Ti type, a medium entropy alloy or high entropy alloy of BCC type, or a medium entropy alloy or high entropy alloy of BCC and HCP dual phase. The rest is the same as specific embodiments 1 to 3.

[0038] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the electrolyte described in step 1 is composed of disodium ethylenediaminetetraacetic acid, calcium acetate, sodium tungstate, sodium hexametaphosphate, sodium hydroxide and deionized water, and the concentration of disodium ethylenediaminetetraacetic acid in the electrolyte is 8g / L-20g / L, the concentration of calcium acetate is 4g / L-15g / L, the concentration of sodium tungstate is 2g / L-20g / L, the concentration of sodium hexametaphosphate is 5g / L-20g / L, and the concentration of sodium hydroxide is 5g / L-20g / L. Others are the same as specific embodiments 1 to 4.

[0039] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: in step 1, micro-arc oxidation is performed for 5 min to 40 min under the conditions of a current of 0.5 A to 2.5 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20° C. to 30° C. The rest is the same as specific embodiments 1 to 5.

[0040] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the tungstate solution described in step 2 is a sodium tungstate solution or a potassium tungstate solution; the concentration of the tungstate solution described in step 2 is 0.01 mol / L to 3.0 mol / L. The rest is the same as specific embodiments 1 to 6.

[0041] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that in step 2, the titanium plate treated with micro-arc oxidation is immersed in a tungstate solution and subjected to microwave hydrothermal treatment for 1 h to 8 h at a power of 200 W to 1000 W and a temperature of 60° C. to 200° C. The rest is the same as specific embodiments 1 to 7.

[0042] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the acid solution in step 3 is hydrochloric acid, sulfuric acid and phosphoric acid; the concentration of the acid solution in step 3 is 6 mol / L to 12 mol / L. Others are the same as specific embodiments 1 to 8.

[0043] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that in step 3, the titanium plate after microwave hydrothermal treatment is immersed in an acid solution at a temperature of 20°C to 80°C for 6min to 18min. The rest is the same as Specific embodiments 1 to 9.

[0044] The following examples are used to verify the beneficial effects of the present invention:

[0045] Embodiment 1:

[0046] A method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface is carried out in the following steps:

[0047] 1. Micro-arc oxidation treatment:

[0048] The pretreated titanium plate was placed in an electrolyte, with the pretreated titanium plate as an anode and the stainless steel plate as a cathode, and micro-arc oxidation was performed for 20 minutes in a pulse constant current mode under the conditions of a current of 2.0 A, a pulse frequency of 800 Hz, a duty cycle of 8%, and an electrolyte temperature of 30° C., to obtain a titanium plate treated with micro-arc oxidation;

[0049] The electrolyte is composed of disodium ethylenediaminetetraacetate, calcium acetate, sodium tungstate, sodium hexametaphosphate, sodium hydroxide and deionized water, and the concentration of disodium ethylenediaminetetraacetate in the electrolyte is 12 g / L, the concentration of calcium acetate is 4.4 g / L, the concentration of sodium tungstate is 12 g / L, the concentration of sodium hexametaphosphate is 10 g / L, and the concentration of sodium hydroxide is 5 g / L;

[0050] The pretreated titanium plate is specifically prepared according to the following steps: polishing the surface of the titanium plate with 400# and 1000# metallographic sandpaper in sequence, then washing with deionized water, and finally drying at a temperature of 25° C. for 0.5 h to obtain a pretreated titanium plate;

[0051] The titanium plate is HCP type titanium;

[0052] 2. Microwave hydrothermal treatment:

[0053] The titanium plate treated by micro-arc oxidation was immersed in a tungstate solution, and subjected to microwave hydrothermal treatment for 3 h at a power of 600 W and a temperature of 200 ° C to obtain a titanium plate treated by microwave hydrothermal treatment;

[0054] The tungstate solution is a sodium tungstate solution; the concentration of the tungstate solution is 0.5 mol / L;

[0055] 3. Ion exchange treatment:

[0056] Under the condition of temperature of 70°C, the titanium plate after microwave hydrothermal treatment was immersed in an acid solution for 12 minutes, and finally washed and dried to obtain the titanium plate after ion exchange treatment;

[0057] The acid solution is hydrochloric acid; the concentration of the acid solution is 12 mol / L;

[0058] 4. Heat treatment:

[0059] The titanium plate after ion exchange was placed in a muffle furnace and heat treated for 5 hours in an air atmosphere at a temperature of 600°C to obtain a ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface.

[0060] Figure 1This is the EDS spectrum of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in Example 1; as can be seen from the figure, trace elements such as calcium and tungsten have been successfully introduced into the coating.

[0061] Figure 2 This is the XRD spectrum of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in Example 1, A is the anatase peak, B is the titanium peak, C is calcium tungstate, and D is tungsten oxide. As can be seen from the figure, XRD diffraction detection shows that calcium tungstate and tungsten oxide exist in the sample treated in this example.

[0062] Figure 3 This is a scanning electron microscope image of the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface of Example 1; as can be seen from the scanning photo, a large amount of blade-shaped calcium tungstate and granular tungsten oxide are formed on the coating surface.

[0063] A titanium plate or a ternary TiO2 / CaWO3 / WO3 heterostructure constructed on a titanium surface after micro-arc oxidation treatment with a size of 10 mm×10 mm was placed in 10 mL of a 10 mg / mL subunit blue solution and irradiated with a xenon lamp with a power of 300 W for 120 min. The light response intensity of the ternary heterostructure was evaluated based on the degradation ability of the organic dye. Figure 4 The organic dye degradation rate of the titanium plate treated with micro-arc oxidation prepared in step 1 of Example 1 and the ternary TiO2 / CaWO3 / WO3 heterostructure constructed on the titanium surface in step 4. Compared with the sample with only titanium dioxide on the titanium plate treated with micro-arc oxidation, the degradation rate of organic dyes can reach 88%. This shows that the sample obtained in this example has a certain light response intensity.

[0064] Embodiment 2: This embodiment differs from Embodiment 1 in that in step 1, the micro-arc oxidation is performed for 20 minutes under the conditions of a current of 2.0 A, a pulse frequency of 600 Hz, a duty cycle of 8%, and an electrolyte temperature of 20° C. The rest is the same as Embodiment 1.

[0065] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 80%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0066] Embodiment 3: This embodiment is different from Embodiment 1 in that the concentration of disodium ethylenediaminetetraacetate in the electrolyte in step 1 is 15 g / L, and the concentration of calcium acetate is 8.8 g / L. Others are the same as Embodiment 1.

[0067] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 82%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0068] Embodiment 4: This embodiment is different from Embodiment 1 in that the concentration of the tungstate solution in step 2 is 1.0 mol / L. The rest is the same as Embodiment 1.

[0069] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 85%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0070] Embodiment 5: This embodiment is different from Embodiment 1 in that the concentration of the sodium tungstate solution in step 2 is 3.0 mol / L. The rest is the same as Embodiment 1.

[0071] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 80%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0072] Embodiment 6: This embodiment is different from Embodiment 1 in that the acid solution in step 3 is hydrochloric acid with a concentration of 8 mol / L. The rest is the same as Embodiment 1.

[0073] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 83%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0074] Embodiment 7: This embodiment is different from Embodiment 1 in that the soaking temperature in step 3 is 80° C. The rest is the same as Embodiment 1.

[0075] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 86%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0076] Embodiment 8: This embodiment is different from Embodiment 1 in that the soaking time in step 3 is 18 minutes. The rest is the same as Embodiment 1.

[0077] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 84%. It shows that the sample obtained in this embodiment has a certain light response intensity.

[0078] Embodiment 9: This embodiment differs from Embodiment 1 in that: in step 4, the heat treatment is performed for 8 hours in an air atmosphere at a temperature of 800° C. The rest is the same as Embodiment 1.

[0079] The sample treated in this embodiment was tested by EDS spectrum, and trace elements such as calcium and tungsten were successfully introduced into the coating. XRD diffraction detected the presence of calcium tungstate and tungsten oxide in the sample treated in this embodiment. Scanning electron microscopy showed that a large amount of leaf-shaped calcium tungstate and granular tungsten oxide were formed on the surface of the coating. The light response ability of the sample surface treated in this embodiment was characterized by the same test method as in Example 1, and the degradation rate of the organic dye could reach 85%. It shows that the sample obtained in this embodiment has a certain light response intensity.

Claims

1. A method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface, characterized in that It is carried out in the following steps:

1. Micro-arc oxidation treatment: The pretreated titanium plate is placed in an electrolyte, the pretreated titanium plate is used as an anode, the stainless steel plate is used as a cathode, and a pulse constant current mode is adopted to perform micro-arc oxidation under the conditions of a current of 0.5A to 2.5A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C, to obtain a titanium plate treated with micro-arc oxidation; The electrolyte is composed of ethylenediaminetetraacetate, acetate, tungsten salt, metaphosphate, alkali solution and deionized water; 2. Microwave hydrothermal treatment: The titanium plate treated by micro-arc oxidation is immersed in a tungstate solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment; 3. Ion exchange treatment: The titanium plate after microwave hydrothermal treatment is immersed in an acid solution, and finally washed and dried to obtain the titanium plate after ion exchange treatment; 4. Heat treatment: The titanium plate after ion exchange is placed in a muffle furnace and heat treated for 1h to 8h in an air atmosphere at a temperature of 300°C to 800°C, thereby completing the method of in-situ construction of a light-responsive ternary heterostructure on the titanium surface.

2. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that The pretreated titanium plate described in step 1 is specifically prepared according to the following steps: polishing the surface of the titanium plate with 400# and 1000# metallographic sandpaper in turn, then washing it with deionized water, and finally drying it at a temperature of 20°C to 30°C for 0.5h to 1h to obtain a pretreated titanium plate.

3. A method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 2, characterized in that The titanium plate is made of titanium, titanium alloy, titanium-based medium-entropy alloy or titanium-based high-entropy alloy.

4. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 2, characterized in that The titanium plate is a HCP-Ti type medium entropy alloy or high entropy alloy, a BCC-Ti type medium entropy alloy or high entropy alloy, a BCC type medium entropy alloy or high entropy alloy, or a BCC and HCP dual-phase medium entropy alloy or high entropy alloy.

5. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that The electrolyte described in step 1 is composed of disodium ethylenediaminetetraacetic acid, calcium acetate, sodium tungstate, sodium hexametaphosphate, sodium hydroxide and deionized water, and the concentration of disodium ethylenediaminetetraacetic acid in the electrolyte is 8g / L~20g / L, the concentration of calcium acetate is 4g / L~15g / L, the concentration of sodium tungstate is 2g / L~20g / L, the concentration of sodium hexametaphosphate is 5g / L~20g / L, and the concentration of sodium hydroxide is 5g / L~20g / L.

6. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that In step 1, micro-arc oxidation is performed for 5 min to 40 min under the conditions of a current of 0.5 A to 2.5 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20% and an electrolyte temperature of 20° C. to 30° C.

7. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that The tungstate solution described in step 2 is a sodium tungstate solution or a potassium tungstate solution; the concentration of the tungstate solution described in step 2 is 0.01 mol / L to 3.0 mol / L.

8. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that In step 2, the titanium plate after micro-arc oxidation treatment is immersed in a tungstate solution, and microwave hydrothermal treatment is performed for 1 h to 8 h at a power of 200 W to 1000 W and a temperature of 60° C. to 200° C.

9. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that The acid solution described in step 3 is hydrochloric acid, sulfuric acid and phosphoric acid; the concentration of the acid solution described in step 3 is 6 mol / L to 12 mol / L.

10. The method for in-situ construction of a photoresponsive ternary heterostructure on a titanium surface according to claim 1, characterized in that In step three, the titanium plate after microwave hydrothermal treatment is immersed in an acid solution at a temperature of 20° C. to 80° C. for 6 min to 18 min.

Citation Information

Patent Citations

  • Visible-light-responsive photocatalyst powder, process for producing the same, and visible-light-responsive photocatalyst material, photocatalytic coating material, and photocatalytic product each containing the same

    CN101821005A

  • Method for preparing macroscopical porous micro-arc oxidation coating based on two-step process

    CN103046102A

  • Heterojunction coating capable of spontaneously generating discrete electric field and preparation method thereof

    CN118241279A

  • Visible-light response photocatalyst powder and visible-light response photocatalyst material, photocatalytic coating material, and photocatalytic article each using the same

    JP2009233655A

  • METHOD FOR PRODUCING PHOTOCATALYST BASED ON NANO-HETEROSTRUCTURAL SEMICONDUCTOR CdS-WO3-TiO2

    RU2624620C1